National Economic Resilience in the Face of Global Crises: A Policy Analysis Based on IMF and World Bank Reports - Fadli Agus Triansyah; Karyono Karyono (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the determinants of national economic resilience in the context of recurrent global crises through an empirical cross-country panel analysis integrating macroeconomic indicators and systematic policy text evaluation. Using data from IMF and World Bank databases covering 2005–2024, the research constructs a composite resilience index based on output volatility, recovery speed, fiscal adjustment, and financial stability metrics. A policy alignment index derived from structured content analysis of Article IV consultations and flagship reports captures the degree of coherence between multilateral recommendations and national policy orientations. Panel regression models, instrumental variable techniques, and dynamic system GMM estimations are employed to address endogeneity and persistence effects. The findings indicate that fiscal space, governance quality, financial depth, and digitalization significantly enhance resilience outcomes, while stronger alignment with multilateral policy guidance is associated with faster recovery and reduced macroeconomic instability. The results contribute to the literature on economic resilience by empirically linking institutional policy coordination with measurable stabilization performance, offering evidence-based insights for strengthening adaptive macro-financial governance frameworks in an era of systemic uncertainty.